Analisis Trending Topic di Twitter: #NTTBerduka Pada Studi Kasus #BanjirBandang di NTT 2021 - Riyani, Alfirda (Universitas Semarang, 2021)
The social media Twitter is the most actively used in Indonesia. Users are often involved in hot topics discussed in cyberspace. No wonder the trending topic on Twitter is dominated by topics from Indonesia. Natural phenomena often occur in Indonesia in early 2021, one of which is the flash flood that occurred in NTT a few days ago. With this phenomenon, it has made new trending topics, namely #NTTBerduka and #BanjirBandang, which are warmly discussed by Twitter users. This research uses quantitative methods with social network analysis techniques, the visualization of the network will be in the form of graphs. Data is taken on netlytic.com which does not pay, the data is crawled which shows 10000 tweets and data retrieval in the past 1 week. The results of the study concluded that there were many netizens who thought that they felt sorry for the banjir bandang that hit in NTT and they also prayed for the victims to be found soon